Faktor-Faktor Internal Yang Berpengaruh Terhadap Keberhasilan Menghafal al-Qur’ân Siswa Madrasah Tsanawiyah - Falah, Ahmad (Tarbawiyah Jurnal Ilmiah Pendidikan, 2021)
The success of memorizing the Qur'an is not only determined by the ability of students to memorize, but there are other factors more important than that, namely internal factors that directly affect the soul and attitudes of students, namely rote learning background, learning motivation and self effication student. Besides the factor of their understanding of memorized verses. The understanding of memorized verses depends on students 'understanding of Arabic, because the Qur'an uses Arabic, therefore students' understanding of Arabic will facilitate students in memorizing the Qur'an and successfully memorizing it.